Factor Analysis of Collaborative Working of Teachers in The New Normal - Khotta, Weerasak; Masantiah, Chuthaphon; Panidvadtana, Panida (Interdisciplinary Academic and Research Journal, 2023)
Professional Learning Community (PLC) emphasizes the collaboration of administrators, teachers, and stakeholders in developing their own professional practice with fellow teachers. The exchange of knowledge, skills, and experiences necessary for professional development and professional knowledge. The current research endeavor aimed to investigate factors of collaborative working of teachers in the new normal era. The sample included 976 teachers working in private schools under the Office of the Private Education Commission in Bangkok’s subcenter 11 of the general education system in 2021. The research employed a 5-Likert scale questionnaire with an IOC value of 1.00 and a validity value of 0.950. The data were analyzed using EFA, orthogonal rotation, and varimax rotation. The research results revealed seven factors of collaborative working among teachers under the Office of the Private Education Commission in the new normal: self-awareness, compassion, online communication, self-adaptation, feedback, technological tools, and humility. Together these factors accounted for 67.175% of the variance. Moreover, it was also found that humility was the lowest mean among all components. Emphasis should be placed on encouraging teachers to reduce self-esteem in working with others. to create cooperation and unite in the work of teachers further efficiently.